DICER1 syndrome and its various paediatric presentations: Case series and review of the literature - Courtney L. Willis; Angela K. Lucas-Herald; Chamidri Naotunna; Suet Ching Chen; Rosemarie Davidson; Jairam Sastry; Dermot Murphy; M.Guftar Shaikh; Milind Ronghe (EJC Paediatric Oncology, 2024)
DICER1 syndrome is a rare tumour predisposition syndrome, associated with a range of benign and malignant tumours, which may occur during childhood. A high index of suspicion is required to ensure appropriate diagnosis and testing, with early treatment and surveillance of at-risk individuals. In this report, we present 5 patients with variants in DICER1 identified following diagnosis of a minimally invasive thyroid follicular cell carcinoma, a pineoblastoma, a pleuropulmonary blastoma, a urethral rhabdomyosarcoma and on sibling testing. Each of these children have presented at a young age, and 2 have presented with characteristic tumours prior to the ages currently recommended for initiation of routine screening. We discuss their presentation, management and follow up, as well as a review of the current literature on each associated tumour in relation to our patients. Overall, we demonstrate that DICER1 is a heterogenous condition and that there is a need for cascade testing of family members as well as regular screening for tumour development in affected children, although consideration should be made regarding initiating this screening at an earlier age depending on clinical findings.